Stimulasi Tunas Eksplan Kalus Cendana (Santalum album L.) Secara In Vitro dengan 2-Isopentenyladenine (2-iP) - Adriani, Ida Ayu Sri Dewi; Dwiyani, Rindang; Darmawati, Ida Ayu Putri (Nandur, 2022)
Sandalwood ( Santalum album L. ) grows naturally in Indonesia, especially in Nusa Tenggara Timur area and this is one of 22 Santalum genus species in the world. Aim of the study is to determine the effect of 2-iP and the best concentration of 2-iP to stimulate callus explant shoots of Santalum album L . This studies carried out from September 2019 up to February 2020, the explants used were callus from bud culture from previous studies. The explants were planted at the Tissue Culture Laboratory, Faculty of Agriculture Udayana University Pulau Moyo street, Denpasar. This study used a completely randomized design (CRD) with 5 treatments, namely: (2-iP 0.0 ppm, 2-iP 0.5 ppm, 2-iP 1.0 ppm, 2-iP 1.5 ppm, 2-iP 2.0 ppm). The results showed that the addition of ZPT 2iP on WPM + 0.01 ppm NAA had a significant and very significant effect on the number of shoots, number of leaves and shoot length and had no significant effect on the emergence of shoots. The M 1 treatment (WPM + 0.01 ppm NAA + 0.5 ppm 2-iP) showed the fastest time (1,55 MST) for the emergence of shoots on sandalwood callus explants. Treatment without the addition of zpt 2-iP (M 0 ) could increase the number of shoots (2.87 pieces), number of leaves (5.59 strands) and shoot length (1.64 cm).